Security measures as a factor in the competitiveness of accommodation facilities - Rafał Nagaj; Brigita Žuromskaitė (Journal of Risk and Financial Management, 2020)
The main aim of this article was to assess whether the level of competitiveness of accommodation facilities results from the level of safety and security provided to consumers of these services, measured by the number of security measures applied in them. The authors' task was to examine the level of concentration of security measures in the accommodation facilities and to assess whether the quality of services measured by the star-rating system provided a higher level of safety and security for customers of the accommodation facilities, measured by the number of security measures applied in them. It was decided to examine whether the level of concentration of security measures at the accommodation facilities was treated by these entities as a factor of their competitiveness. Two locations in Central and Eastern Europe, one in Poland and one in Lithuania, were analyzed. The article calculated the frequency of these measures at the accommodation facilities by type of facility (according to the star-rating system) and type of security measure (as a weighted average) and their concentration using the Herfindahl-Hirscham Index. The results showed that the higher the quality of services provided (more stars), the higher the level of safety and security is ensured. It was also found that a higher level of security was not reflected in the prices of accommodation services.
Keywords: 330; accommodation; security measures; level of competitiveness